A DUAL COX-2/sEH INHIBITOR IMPROVES THE METABOLIC PROFILE AND REDUCES KIDNEY INJURY IN ZUCKER DIABETIC FATTY RAT - Khan, Md. Abdul Hye (Prostaglandins Other Lipid Mediat, 2016)
Cyclooxygenase (COX) and soluble epoxide hydrolase (sEH) inhibitors have therapeutic potential. The present study investigated efficacy of a novel dual acting COX-2/sEH inhibitor, PTUPB in type 2 diabetic Zucker Diabetic Fatty (ZDF) rats. Male ZDF rats were treated with vehicle or PTUPB (10 mg/kg/d, i.p.) for 8 weeks. At the end of the 8-week experimental period, ZDF rats were diabetic (fasting blood glucose, 287±45 mg/dL) compared to Zucker Diabetic Lean rats (ZDL, 99±6 mg/dL), and PTUPB treatment improved glycemic status in ZDF rats (146±6 mg/dL). Kidney injury was evident in ZDF compared to ZDL rats with elevated albuminurea (44±4 vs 4±2 mg/d) and nephrinurea (496±127 vs 16±4 μg/d). Marked renal fibrosis, tubular cast formation and glomerular injury were also present in ZDF compared to ZDL rats. In ZDF rats, PTUPB treatment reduced kidney injury parameters by 30–80% compared to vehicle. The ZDF rats also demonstrated increased inflammation and oxidative stress with elevated levels of urinary monocyte chemoattractant protein-1 excretion (862±300 vs 319±75 ng/d), renal macrophage infiltration (53±2 vs 37±4 /mm(2)) and kidney malondialdehyde/protein ratio (10±1 vs 5±1 μmol/mg). PTUPB treatment decreased these inflammatory and oxidative stress markers in the kidney of ZDF rats by 25–57%. These data demonstrate protective actions of a novel dual acting COX-2/sEH inhibitor on the metabolic abnormalities and kidney function in ZDF rat model of type 2 diabetes.